Hydrodynamic Modelling-Based Prediction and Evaluation of Post-Normalisation Sedimentation in Badeng River with HEC-RAS - Zulis Erwanto; Puthut Omar Satriawan; Mohammad Anwar Fathoni (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
The Badeng River in Banyuwangi, Indonesia, has experienced rapid sediment re-accumulation after the 2022 normalization works. This study evaluates post-normalization sedimentation using a one-dimensional HEC-RAS sediment transport model supported by field surveys, sediment sampling, river geometry data, and dredging records. The model predicted annual sediment accumulation of 4,494.88 m³/year at Pakel and 4,380.02 m³/year at Garit. Comparison with dredging records produced a mean absolute error of 1,271.27 m³, corresponding to a deviation of approximately 38–42%. This deviation reflects combined uncertainty from DEM-derived channel geometry, localized excavation records, and excavator-bucket-based dredging volume estimation. Despite this uncertainty, the simulated deposition pattern was consistent with field observations and confirmed substantial sediment recovery within three years after normalization. The results indicate that 1D HEC-RAS is suitable as a decision-support tool for identifying sedimentation-prone reaches, planning dredging intervals, and supporting sediment management in data-limited tropical rivers.